Kudal Commission of Inquiry on Gandhi Peace Foundation and Other Organisations Fifth Interim Report - Planning Commission (Planning Commission, 1986)
The present report is the fifth in a series of Interim Reports submitted by this Commission to the Union Government. The first four Interim Reports were submitted on 4-1-1985, 25-4-1985, 15-7-1985 and 16-12-1985 respectively. The present report covers the progress made by this Commission in the matter of investigations and inquiries upto 18th April, 1986.
Fifth Interim Report
Fifth Interim Report